The likelihood of admission of elderly persons to a psychiatric hospital : a comparative study of elderly persons admitted for the first time to a psychiatric hospital and of elderly persons in the community, with special reference to the composition, organisation, and structural integration of their families - Elk, Ronith (Department of Social Development, 2016)
The helping professions in many parts of the world, experience concern over the increased number of admissions of elderly patients to psychiatric hospitals. This study has been prompted by similar concern in Cape Town. Although old people have always suffered from psychiatric illnesses, the problem becomes more acute as the numbers of elderly rise, especially in industrialised countries. A noticeable and alarming trend, particularly in the last three decades, has been the rise in first admissions of old people to psychiatric hospitals. Over the period 1978 to 1980, a multidisciplinary project in which the writer was appointed as a research worker, was conducted by the Department of Psychiatry in the University of Cape Town. This project was conducted in both the Psychogeriatric Unit of Valkenberg Hospital and in suburbs of Cape Town from the same catchment area that the hospital serves. The aim of the project was, to examine the possible contributory reasons for psychiatric illness that led to consequent hospitalisation of the elderly. It covered a multitude of psychiatric, physical, and psychosocial variables. Over the same period, the author conducted a separate but associated research, focusing on one specific psychosocial variable - that of the family of the old person. This variable was selected as the nucleus of the study for two major reasons.